Connecting Turbulence and Meandering Parameterization to Describe Passive Scalars Dispersion in Low Wind Speed Conditions. (14th January 2013) - Moreira, V. S.; Degrazia, G.; Timm, A. U.; Roberti, D. R.; Maldaner, S.
Abstract : The following study deals with meandering of the horizontal mean wind. The main motivation for such investigation came from the difficulty in describing contaminant dispersion in meandering conditions. Observational field measurements point out that the autocorrelation function of the horizontal wind components, obtained for the meandering cases, displays an oscillating behavior with the presence of large negative lobes. Such negative lobes are described by an equation containing functions that represent patterns of movement associated to meandering and turbulence. As a consequence, this mathematical formulation connects the turbulence and meandering phenomenon establishing the employment of hybrid parameters in models that describe the meandering dispersion. Therefore, considering this dualistic aspect between meandering and turbulence manifestations, a new set of relations for the turbulence parameterization joined with the meandering of the wind have been developed and are available. This new turbulence parameterization for a stable shear forcing planetary boundary layer, united with a meandering mean time scale is able to describe contaminant meandering enhanced spread in a low wind speed stable planetary boundary layer.